2008
DOI: 10.1038/nrm2438
|View full text |Cite
|
Sign up to set email alerts
|

Ras oncogenes: split personalities

Abstract: Extensive research on the Ras proteins and their functions in cell physiology over the past 30 years has led to numerous insights that have revealed the involvement of Ras not only in tumorigenesis but also in many developmental disorders. Despite great strides in our understanding of the molecular and cellular mechanisms of action of the Ras proteins, the expanding roster of their downstream effectors and the complexity of the signalling cascades that they regulate indicate that much remains to be learnt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
1,254
1
35

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,319 publications
(1,304 citation statements)
references
References 223 publications
(194 reference statements)
14
1,254
1
35
Order By: Relevance
“…While point mutations in codon 12 or 13 account for the majority of KRAS mutations (8), recent studies have reported that KRAS also undergoes copy number gain at chromosome 12p12 in 11% to 15% of lung tumors (9,10). RAS genes are members of the small GTPase super family (11) and function to propagate growth factor signaling through activation of c-RAF and phosphoinositide-3-kinase (PI3K) pathways. Despite concerted efforts, KRAS mutation defines a genetic subtype of lung cancer that is currently not amenable to therapeutic intervention (12).…”
Section: Introductionmentioning
confidence: 99%
“…While point mutations in codon 12 or 13 account for the majority of KRAS mutations (8), recent studies have reported that KRAS also undergoes copy number gain at chromosome 12p12 in 11% to 15% of lung tumors (9,10). RAS genes are members of the small GTPase super family (11) and function to propagate growth factor signaling through activation of c-RAF and phosphoinositide-3-kinase (PI3K) pathways. Despite concerted efforts, KRAS mutation defines a genetic subtype of lung cancer that is currently not amenable to therapeutic intervention (12).…”
Section: Introductionmentioning
confidence: 99%
“…RAS-activating mutations, especially KRAS mutations, are one of the most prevalent genetic changes found in cancer, occurring in about 20% of human tumours (Downward, 2003;Karnoub and Weinberg, 2008). In these tumours, the activated RAS protein contributes significantly to several aspects of the malignant phenotype, including the deregulation of tumour cell growth, invasiveness and the ability to induce new blood-vessel formation, and the suppression of programmed cell death.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Added to this, the experimental evidence substantiating the importance of the Ras-ERK pathway in cancer initiation and progression is overwhelming: activated mutants of Ras, Raf, and MEK have been shown to induce malignant transformation in many cell types. Studies using genetic and pharmacological interference of the Ras-ERK pathway have demonstrated that its signals are essential for the maintenance of the transformed phenotype in diverse tumor-derived cells, [1,2] and sophisticated animal models have endorsed the importance of this pathway for tumorigenesis in vivo. [3] Thus, it is hardly surprising that this signaling cascade has attracted enormous attention for antineoplastic intervention.…”
Section: Introductionmentioning
confidence: 99%